Squamous Cell Carcinoma Arising From A Burns Scar And Presenting As A Cutaneous Horn - Yesudian P D; Krishnan S G S; Jayaraman M; Janaki V R; Raj Boopal J M (Wolters Kluwer Medknow Publications, 1995)
A34 year old women presented to the Dermatology O.P. with a burns scar of duration more than 3 decades. She had developed a horny excrescence from this scare for the past 6 months. Histopathlogy of the base of the lesion showed evidence of a squamous cell carcinoma. This case is reported to stress the need for long term follows up of all cases of burns scars due to potentially lethal complication of malignant transformation.